Metabolic Fate of [(14)C]Cefamandole, a Parenteral Cephalosporin Antibiotic, in Rats and Dogs - Sullivan, H. R. (1977)
The biotransformation of the parenterally effective cephalosporin antibiotic cefamandole nafate (I) has been studied in rats and dogs. After rapid in vivo hydrolysis of the nafate pharmaceutical form to cefamandole (II), the antibiotic was found to be very resistant to metabolic degradation in both species. In dogs, cefamandole escaped metabolism and was eliminated as unaltered antibiotic almost exclusively by renal excretion. In rats, cefamandole was somewhat labile to metabolism; however, a major portion of the administered antibiotic was eliminated unchanged principally by renal excretion.